Lithium in drinking water and the incidence of bipolar disorder: A nation‐wide population‐based study. (17th July 2017) - Kessing, Lars V; Gerds, Thomas A; Knudsen, Nikoline N; Jørgensen, Lisbeth F; Kristiansen, Søren M; Voutchkova, Denitza; Ernstsen, Vibeke; Schullehner, Jörg; Hansen, Birgitte; Andersen, Per K; Ersbøll, Annette K
Abstract : Objective: Animal data suggest that subtherapeutic doses, including micro doses, of lithium may influence mood, and lithium levels in drinking water have been found to correlate with the rate of suicide. It has never been investigated whether consumption of lithium may prevent the development of bipolar disorder (primary prophylaxis). In a nation‐wide population‐based study, we investigated whether long‐term exposure to micro levels of lithium in drinking water correlates with the incidence of bipolar disorder in the general population, hypothesizing an inverse association in which higher long‐term lithium exposure is associated with lower incidences of bipolar disorder. Methods: We included longitudinal individual geographical data on municipality of residence, data from drinking water lithium measurements and time‐specific data from all cases with a hospital contact with a diagnosis of mania/bipolar disorder from 1995 to 2013 (N=14 820) and 10 age‐ and gender‐matched controls from the Danish population (N= 140 311). Average drinking water lithium exposure was estimated for all study individuals. Results: The median of the average lithium exposure did not differ between cases with a diagnosis of mania/bipolar disorder (12.7 μg/L; interquartile range [IQR]: 7.9‐15.5 μg/L) and controls (12.5 μg/L; IQR: 7.6‐15.7 μg/L; P =.2). Further, the incidence rate ratio of mania/bipolar disorder did not decrease with higher long‐term lithium exposure, overall, or within age categories (0‐40, 41‐60 and 61‐100 years of age). Conclusion: Higher long‐term lithium exposure from drinking water was not associated with a lower incidence of bipolar disorder. The association should be investigated in areas with higher lithium levels than in Denmark.